Proposal of a design model for masonry walls subjected to in-plane loading - Haach, V. (2013)
Masonry walls subjected to in-plane loading exhibit a complex behavior because of the influence of several parameters such as axial load, aspect ratio, and the strength of materials. In high-rise buildings or seismic areas, large tensile stresses may arise in these walls, and vertical and horizontal reinforcement is often used to provide proper resistance, which increases the complexity of the structural behavior. This work presents (1) an overview of the experimental behavior of unreinforced and reinforced masonry walls; (2) an overview of distinct design methods aimed at calculating the in-plane lateral resistance; and (3) a proposal of a new design model for reinforced masonry walls subjected to in-plane loading. The proposed model considers the coupling interaction of the flexural and shear resisting mechanisms and updates the role of the vertical and horizontal reinforcement to the lateral resistance. A database composed of experimental results of the in-plane lateral resistance of 101 masonry walls available in the literature was used to evaluate the performance of existing models and to validate the newly proposed model, which exhibits much better performance.